Body mass index as a predictor of the presence but not the severity of coronary artery disease evaluated by cardiac computed tomography. (November 2014) - Dores, Hélder; de Araújo Gonçalves, Pedro; Carvalho, Maria Salomó; Sousa, Pedro Jerónimo; Ferreira, António; Cardim, Nuno; Carmo, Miguel Mota; Aleixo, Ana; Mendes, Miguel; Machado, Francisco Pereira; Roquette, José; Marques, Hugo
Background: The relation between body mass index (BMI) and coronary artery disease (CAD) extension remains controversial. The aim of this study was to evaluate the correlation between BMI and CAD extension documented by coronary computed tomography angiography (CCTA). Methods and results: Prospective registry including 1706 consecutive stable patients that performed CCTA (dual source scanner) for the evaluation of CAD. The population was stratified by BMI: normal 530 (31.1%), overweight 802 (47.0%) and obesity 374 (21.9%). BMI was significantly higher in patients with CAD (27.7 ± 4.3 vs 26.8 ± 4.3 kg/m 2, p < 0.001); these patients were also older, more often male and had higher prevalence of diabetes, hypertension and dyslipidemia. By multivariate analysis (logistic regression) BMI remains an independent predictor of CAD (odds ratio (OR) 1.03, 95% confidence interval (CI) 1.01–1.06; p = 0.012). Regarding the severity of CAD, BMI was not significantly different among patients with and without obstructive CAD (27.7 ± 4.3 vs 27.2 ± 4.3 kg/m 2, p = 0.120). In 319 patients (4516 segments; 4077 evaluable), a detailed atherosclerotic burden was evaluated and compared among BMI classes, defined according to the presence of plaque and the degree of stenosis. Obstructive CAD was identified in 16.9% of the patients and 45.1% had non-obstructive CAD. The discriminative threshold for high burden, established by the segment involvement score (SIS), was >5 segments with plaque (15.4% patients). The prevalence of SIS >5 among the BMI classes was: 18.7%, 13.7% and 13.6% for normal, overweight and obesity respectively ( p values for the specific classes versus all other patients: 0.241, 0.450 and 0.663). Conclusions: In this population of stable patients undergoing CCTA for suspected CAD, BMI was an independent predictor of its presence, but was not correlated with the coronary disease severity.